Sobre a perda da grandiloquência na literatura hispano-americana pós-noventa: notas sobre a des-representação do exílio em Lemebel e Bolaño - Pablo Gasparini (Estudos de Literatura Brasileira Contemporânea)
The aim of this article is to analyze the transition from the political comprehension of the Hispanic-American Literature on the ’80 to another paradigm that involves speci fi c changes on the functions and characteristics of the literary discourse due to the Latin-American democratization and the strengthening of the mass culture. For this aim, will be done references to the exile representations on Respiración ar- ti fi cial by Ricardo Piglia; Loco afán. Crónicas de sidario by Pedro Lemebel, and 2666 and the short story “El Ojo Silva” by Roberto Bolaño.